2014
DOI: 10.5624/isd.2014.44.4.279
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of CT numbers in limited and medium field-of-view scans taken using Accuitomo 170 and Veraviewepocs 3De cone-beam computed tomography scanners

Abstract: PurposeTo assess the influence of anatomic location on the relationship between computed tomography (CT) number and X-ray attenuation in limited and medium field-of-view (FOV) scans.Materials and MethodsTubes containing solutions with different concentrations of K2HPO4 were placed in the tooth sockets of a human head phantom. Cone-beam computed tomography (CBCT) scans were acquired, and CT numbers of the K2HPO4 solutions were measured. The relationship between CT number and K2HPO4 concentration was examined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
0
17
0
4
Order By: Relevance
“…In the present study, metallic materials in the exomass produced noticeable hypodense and hyperdense streaks (Figures 4-6), which are image artefacts resulting from beam hardening and scattering, as well as data extinction. 22,[27][28][29] For instance, mean voxel value reduced (image darkening) in the presence of any metallic material in the exomass in the CS9300 and Picasso Trio, and in the presence of two cylinders of cobalt-chromium or amalgam in the NewTom Giano. This indicates that hypodense artefacts were more predominant in the image and, in a clinical situation, could possibly affect the diagnosis of hypodense conditions, such as fracture lines.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, metallic materials in the exomass produced noticeable hypodense and hyperdense streaks (Figures 4-6), which are image artefacts resulting from beam hardening and scattering, as well as data extinction. 22,[27][28][29] For instance, mean voxel value reduced (image darkening) in the presence of any metallic material in the exomass in the CS9300 and Picasso Trio, and in the presence of two cylinders of cobalt-chromium or amalgam in the NewTom Giano. This indicates that hypodense artefacts were more predominant in the image and, in a clinical situation, could possibly affect the diagnosis of hypodense conditions, such as fracture lines.…”
Section: Discussionmentioning
confidence: 99%
“…Since such an option is not yet computable on CBCT volumes, its best to use pixel intensity values while keeping in mind that these are not absolutely defined like the Hounsfield units but never the less are practical because many studies have previously shown that Hounsfield units and pixel intensity values have a linear relationship. With careful evaluation and by using some internal controls to define the tissue thresholds, PIV values can be a very reliable way to assess bone density [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…18 Precision, Reproducibility, and Accuracy of Tomographic Bone Plate Level Measurements Recent studies have used higher resolution CBCT images from Accuitomo (J. Morita, Irvine, Calif) to evaluate alveolar bone and have concluded that this method of diagnosis is indicated when selecting the appropriate protocol. 19,20 Our study used the i-Cat Cone Beam 3-D Dental Imaging System (Imaging Sciences International), available at the institution where the project was developed. These results apply only to the i-Cat Cone Beam 3-D Dental Imaging System scanner; a different scanner with similar settings might give different results.…”
Section: Discussionmentioning
confidence: 99%